2013
DOI: 10.1371/journal.pone.0061201
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Influenza A Virus Infection Histories and Long-Term Immune Responses in Mallards

Abstract: Wild dabbling ducks (genus Anas) are the main reservoir for influenza A virus (IAV) in the Northern Hemisphere. Current understanding of disease dynamics and epidemiology in this virus-host system has primarily been based on population-level surveillance studies and infection experiments conducted in laboratory settings. Using a combined experimental-natural approach with wild-strain captive mallards (Anas platyrhynchos), we monitored individual IAV infection histories and immunological responses of 10 birds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 38 publications
4
74
0
Order By: Relevance
“…In addition, the development of partial protection against other strains, defined as heterosubtypic or cross-protective immunity, may also occur [40,[42][43][44][45]. This seems to be true for sentinel mallards in nature [46]. Recently, we showed that this study population develops homo-and heterosubtypic immunity from natural infections [20], and that the heterosubtypic immunity at the HA clade level persists for at least a month.…”
Section: (B) What Is Governing the Seasonal Trends In Influenzamentioning
confidence: 63%
“…In addition, the development of partial protection against other strains, defined as heterosubtypic or cross-protective immunity, may also occur [40,[42][43][44][45]. This seems to be true for sentinel mallards in nature [46]. Recently, we showed that this study population develops homo-and heterosubtypic immunity from natural infections [20], and that the heterosubtypic immunity at the HA clade level persists for at least a month.…”
Section: (B) What Is Governing the Seasonal Trends In Influenzamentioning
confidence: 63%
“…6% prevalence) [27]. Experimental evidence in mallards ( Anas platyrhynchos ) suggests that birds are infected with approximately half of all HA types (6/11) circulating in the population within the first 2 years of life [33]. On average, the AIV prevalence in swans is thought to be considerably lower than the prevalence found in wild mallards [15,49], so it is plausible that the number of infections with different HA types per swan per year is also lower than in mallards.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their importance for poultry, efficient vaccines are available or can be developed against several of these agents. The temporal dynamics and the efficacy of the humoral immune response of chickens to these vaccines can vary greatly (e.g., Walker et al 2010), but very little is known about the dynamics of the humoral immune response in long-lived bird species (Bailey et al 1998;Momayez et al 2007;Garnier et al 2012b;Tolf et al 2013). For instance, whether the long persistence of maternal antibodies reported in a long-lived seabird species (Garnier et al 2012b) is associated with the persistence of high antibody levels in adults would be of interest.…”
Section: Introductionmentioning
confidence: 99%